THE INTERPLAY BETWEEN DIET AND HORMONAL REGULATION: A NARRATIVE REVIEW - Ewa Jagodzińska; Zuzanna Jabłońska; Maja Jabłońska; Julia Kamińska; Joanna Zygadło; Wiktor Milewczyk (International Journal of Innovative Technologies in Social Science, 2025)
Diet is one of the key external factors that can modify hormonal activity across the major endocrine axes and affect metabolic and appetite-regulating hormones including insulin, leptin, ghrelin, and cortisol. A literature search conducted between October and November 2025 using PubMed, Scopus, Web of Science, and Google Scholar identified peer-reviewed studies examining the effects of caloric restriction, macronutrient distribution, glycemic load, micronutrient intake, and structured dietary interventions on endocrine function. The evidence shows that diets high in glycemic load, saturated fats, and low in fiber can disrupt insulin sensitivity, alter leptin and ghrelin signaling, affect cortisol responses, and contribute to thyroid and reproductive hormone imbalances. In contrast, Mediterranean-style and low-glycemic diets, time-restricted feeding, and adequate intake of iodine, selenium, and zinc appear to support metabolic health and more stable hormonal activity. Diet also plays a therapeutic role in endocrine-related conditions including polycystic ovary syndrome, Hashimoto’s disease, acne vulgaris, endometriosis, and thyroiditis, with improvements seen in inflammation, insulin regulation, and hormonal homeostasis. Overall, the review emphasizes that diet can both disturb and restore endocrine balance. Well-structured, nutrient-dense dietary strategies may serve not only as preventive measures but also as valuable tools in supporting long-term hormonal health.